Prespecified Risk Criteria Facilitate Adequate Discharge and Long-Term Outcomes After Transfemoral Transcatheter Aortic Valve Implantation - Spence, Mark S; Baan, Jan; Iacovelli, Fortunato; Martinelli, Gian Luca; Muir, Douglas F; Saia, Francesco; Bortone, Alessandro Santo; Densem, Cameron G; Owens, Colum G; van der Kley, Frank; Vis, Marije; van Mourik, Martijn S; et al. (Journal of the American Heart Association, 2020)
Background Despite the availability of guidelines for the performance of transcatheter aortic valve implantation (TAVI), current treatment pathways vary between countries and institutions, which impact on the mean duration of postprocedure hospitalization. Methods and Results This was a prospective, multicenter registry of 502 patients to validate the appropriateness of discharge timing after transfemoral TAVI, using prespecified risk criteria from FAST-TAVI (Feasibility and Safety of Early Discharge After Transfemoral [TF] Transcatheter Aortic Valve Implantation), based on hospital events within 1-year after discharge. The end point-a composite of all-cause mortality, vascular access-related complications, permanent pacemaker implantation, stroke, cardiac rehospitalization, kidney failure, and major bleeding-was reached in 27.0% of patients (95% CI, 23.3-31.2) within 1 year after intervention; 7.5% (95% CI, 5.5-10.2) had in-hospital complications before discharge and 19.6% (95% CI, 16.3-23.4) within 1 year after discharge. Overall mortality within 1 year after discharge was 7.3% and rates of cardiac rehospitalization 13.5%, permanent pacemaker implantation 4.2%, any stroke 1.8%, vascular-access-related complications 0.7%, life-threatening bleeding 0.7%, and kidney failure 0.4%. Composite events within 1 year after discharge were observed in 18.8% and 24.3% of patients with low risk of complications/early (≤3 days) discharge and high risk and discharged late (>3 days) (concordant discharge), respectively. Event rate in patients with discordant discharge was 14.3% with low risk but discharged late and increased to 50.0% in patients with high risk but discharged in ≤3 days. Conclusions The FAST-TAVI risk assessment provides a tool for appropriate, risk-based discharge that was validated with the 1-year event rate after transfemoral TAVI. Registration URL: https://www.ClinicalTrials.gov; Unique identifier: NCT02404467.
Keywords: Registries; risk; Humans; aortic stenosis; registrace; Evropa; lidé; Europe; Transcatheter Aortic Valve Replacement; propuštění pacienta; transkatetrální implantace aortální chlopně; Postoperative Complications; pooperační komplikace; validation; aortic valve implantation; prospektivní studie; Patient Discharge; discharge; Prospective Studies